Nonprofit Service Continuity and Responses in the Pandemic: Disruptions, Ambiguity, Innovation, and Challenges. (27th August 2020) - Shi, Yu; Jang, Hee S.; Keyes, Laura; Dicke, Lisa
Abstract: This Viewpoint essay examines the service delivery responses of nonprofit organizations that offer homeless support services amid the COVID‐19 pandemic. Government mandates and severe human needs have forced nonprofits to adapt quickly. Literature reviews provide little information about how nonprofits should manage service continuity under pandemics. Data collected from websites and interviews with nonprofits executives provide an understanding of adaptations and innovations. The study uses a crisis response model—"Disruptions‐Ambiguities‐Innovations‐Challenges" (DAIC)—to demonstrate how social service nonprofits are responding to challenges under COVID‐19. Lessons learned are useful for scholars and practitioners to understand ways nonprofits have remained agile and innovative.